Islas Flotantes Artificiales con: Pasto Guinea (Panicum máximum) como alternativa para la remoción de Nitratos y Fosfatos en el agua procedente del río Cutuchi - Ortega Gallegos, Jhony Rodrigo (2019)
Phytoremediation is carried out through physical, chemical and biological processes that take place in the density of its roots, stems and leaves, so that excess nutrients are absorbed by the plant such as nitrates and phosphates. In the present investigation, the system of artificial floating islands (IFAs) with the species guinea grass was implemented, as an alternative to improve the quality of water contaminated by nitrates and phosphates. For the implementation of the IFAs, a greenhouse was built that housed three tubs with their respective floating islands consisting of a floating matrix and substrate. The floating matrix was built with recycled polyvinyl chloride plastic bottles, tubes and meshes. This floating matrix provides a means of growth and stability for the vegetative species under study. The substrate provides an ideal medium for the interrelation of organic matter, plants and microorganisms. The construction of the system is relatively simple, as well as its installation and maintenance, which are considerably economical compared to treatment plants. In Ecuador there are a minimum number of studies carried out for the removal of nitrates and phosphates with alternative systems. This project determined the removal of nitrates and phosphates by means of the grass species Guinea (Panicum maximum) which has given favorable results, with which this project focused on the agricultural sector can be proposed to the population of Latacunga.